The Pengaruh Pupuk kandang Sapi dan NPK 16-16-16 Terhadap Pertumbuhan dan Hasil Terong Hijau di Tanah Berpasir - Nur Rofiq, Muhammad A.U; Hidayat, Nurul; Saijo, Saijo (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
The purpose of this research is to determine the effect of the interaction of two treatment factors, namely cow manure fertilizer and NPK 16-16-16 fertilizer, as well as the effect of each treatment on the growth and yield of green eggplant in sandy soil. The research will be conducted from October 2024 to March 2025, located at the Research and Experimentation Garden (Campus III Muhammadiyah University of Palangkaraya, Jl. Ir. Soekarno No. I, Jekan Raya District, Palangka Raya City, Central Kalimantan). The study will employ a factorial Randomized Block Design consisting of 2 treatment factors, 9 treatment combinations, and 3 groups. The treatments for cow manure fertilizer will consist of 3 levels: 5, 7.5, and 10 tons per hectare. The NPK 16-16-16 fertilizer treatment will have 3 levels: no NPK fertilizer (control), 200, and 300 kg per hectare. The results of the study indicate that the interaction of cow manure and NPK 16-16-16 fertilizers significantly affects growth and yield variables, namely plant height, fruit length, number of fruits, and weight the cultivation of green eggplant. Based on the research conducted, the researchers recommend the use of a manure dose of 7.5 tons per hectare and an NPK fertilizer dosage of 200 kg per hectare.